Hemostatic Changes in Elderly Patients Using Epidural Analgesia and Combined Unilateral Spinal Anesthesia - Rakhmankulov E.J.; Boltaev S.R.,; Bekmurodov F.Y. (Zien Journals, 2022)
Surgical treatment includes rapid activation of the patient, restoration of his ability to stand up, self-care (will), and trophic changes in the skin (bed sores), thromboembolic complications, pulmonary bronchial infection, decompensation of previously compensated organ failure reduces the risk of developing complications. Dystrophic-degenerative diseases also have a negative impact on elderly patients
Keywords: surgical; treatment; dystrophic-degenerative; thromboembolic